2012
DOI: 10.2139/ssrn.2198843
|View full text |Cite
|
Sign up to set email alerts
|

Value for Money? New Microeconometric Evidence on Public R&D Grants in Flanders

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 55 publications
0
35
0
1
Order By: Relevance
“…Their effect is to reduce the marginal cost of R&D investments (Hall and Van Reenen, 2000). By contrast, R&D subsidies target specific projects with high social returns and a longer time horizon, and their effect is to raise the marginal rate of return of R&D (David et al, 2000;Czarnitzki and Lopes-Bento, 2013). An advantage of tax incentives vis-a-vis subsidies is that the former are less subject to policy inefficiencies, since they are bottom up and based on agents' decisions, whereas subsidies are more likely to incur in policy failure because they are highly dependent on the information available to the policy makers that manage the R&D programme and the strategic priorities set by this.…”
Section: The Effects Of Randd Tax Creditsmentioning
confidence: 99%
“…Their effect is to reduce the marginal cost of R&D investments (Hall and Van Reenen, 2000). By contrast, R&D subsidies target specific projects with high social returns and a longer time horizon, and their effect is to raise the marginal rate of return of R&D (David et al, 2000;Czarnitzki and Lopes-Bento, 2013). An advantage of tax incentives vis-a-vis subsidies is that the former are less subject to policy inefficiencies, since they are bottom up and based on agents' decisions, whereas subsidies are more likely to incur in policy failure because they are highly dependent on the information available to the policy makers that manage the R&D programme and the strategic priorities set by this.…”
Section: The Effects Of Randd Tax Creditsmentioning
confidence: 99%
“…2 Many authors have reported that R&D subsidies stimulate private investments (e.g. Almus and Czarnitzki, 2003;Hyytinen and Toivanen, 2005;Czarnitzki, 2006;Görg and Strobl, 2007;Özçelik and Taymaz, 2008;Aerts and Schmidt, 2008;Hussinger, 2008;Meuleman and Maeseneire, 2012;Czarnitzki and Lopes-Bento, 2013), but studies have also found that these funds partly or fully crowd out some private investments (e.g. Wallsten, 2000;Lach, 2002;Busom, 2000;González and Pazó, 2008;Gelabert et al, 2009 Bronzini andIachini, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Propensity score matching (PSM), as a matching method for the estimation of the average treatment effect on the treated (ATT), has been used extensively in empirical studies of the effects of R&D subsidies (see, among others, Aerts and Schmidt;Almus and Czarnitzki, 2003;Carboni, 2011;Czarnitzki and Licht, 2006;Czarnitzki and Lopes Bento, 2013;Duch et al 2009;Duguet, 2004;González and Pazó, 2008;Herrera and Nieto, 2008).…”
Section: Methodsologymentioning
confidence: 99%
“…The wealth of information provided by the PITEC allows an exhaustive set of variables to be selected and similar controls to be included as those used in previous evaluation studies (see, among others, Aerts and Schmidt, 2008;Almus and Czarnitzki, 2003;Antonelli and Crespi, 2013;Czarnitzki and Lopes-Bento, 2013;Czarnitzki and LopesBento, 2014;González and Pazó, 2008;Hussinger, 2008).…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation